Modelling and simulation for autonomous systems : 5th International Conference, MESAS 2018, Prague, Czech Republic, October 17-19, 2018, Revised selected papers /: 5th International Conference, MESAS 2018, Prague, Czech Republic, October 17-19, 2018, Revised selected papers. (2019) - Unknown
No abstract available